Research on the Effects of Neuroglobin on Ferroptosis in the Nerve Cells - Gao, Wenjin; Mo, Chen; Feng, Wei; Pan, Xinmin; Qin, Haojie (Chinese medicine and natural products, 2023)
Objectives The objective of this article was to explore the effects of neuroglobin (NGB) on ferroptosis in the nerve cells.Methods The NGB knockdown model of HT22 cells was constructed, and the ferroptosis-related indexes of cell proliferation activity, contents of iron ion, malondialdehyde (MDA), superoxide and reactive oxygen, and the changes of nuclear factor E2-related factor 2 (Nrf2) expression were examined in the normal group, erastin group, NGB siRNA group, and NGB siRNA + Erastin group, respectively.Results Compared with the normal group, cell proliferation activity and Nrf2 expression were significantly lower in the erastin group, NGB siRNA group, and NGB siRNA + erastin group, and ferroptosis-related indexes such as iron ion content, MDA content, superoxide content, and reactive oxygen species content were significantly reduced, and the difference between NGB siRNA + erastin group, erastin group, and NGB siRNA group was statistically significant (p < 0.05).Conclusion Knockdown of NGB in cells enhances the action of the ferroptosis inducer erastin, and NGB may regulate the cellular ferroptosis process through Nrf2. This research may provide references for the clinical treatment of nervous system disease with Chinese medicine.
Keywords: neuroglobin; HT22 cells; ferroptosis; siRNA; nerve cells